Painful stories: the experience of pain and its narration in the Greek literature of the Imperial period (100-250) - King, D (2011)
This research project investigates the relationship between pain and the practices of explaining and narrating it to others. Current scholarship argues that the representation of suffering became, during the Imperial period, an increasingly effective and popular strategy for cultivating authority and that this explains the success of Christian culture’s representation of itself as a community of sufferers. One criticism of this approach is that the experience of pain has often been assumed, rather than analysed. Here, I investigate the nature of pain by attending to its intimate relationship with language; pain was connected to the strategies used to communicate that experience to others. I will show that writers throughout the Imperial period were concerned with questions about how to communicate pain and how that act of communication shaped, managed, and alleviated the experience. I investigate this culture along three axes. Part 1, ‘The Sublime Representation of Pain’, investigates the way different authors thought about the capacity of sublime language and rhetorical techniques such as enargeia to effectively communicate pain. I argue that for writers such as Longinus, the sublime offers an opportunity to replicate the traumatic experience of the pain sufferer in the audience or listener—pain is narrated to the audience through a traumatic communicative mode. Contrarily, I show how authors such as Plutarch and Galen were particularly concerned to desublimate the representation of pain, reducing the affective power of images of pain by promoting the audience’s conscious engagement with the text or representational medium. Part 2, ‘Medical Narratives’, examines a conflict between Galen and Aristides over the way language and narrative signified or referred to painful experiences. I show how both writers negotiate the way pain destroys and transcends ordered, structured, narrative by engaging in a process of narrative translation. I will illuminate the difference between scientific, diagnostic narratives which explain and rationalise pain experiences (in the case of Galen) and those which attempt to give witness to the nebulous, ineffable qualities of pain. In Part 3, ‘Narrating Cures’ I investigate ancient practices of psychotherapy. I show how various philosophical consolations were underpinned by an understanding of the power of pain to continually return and overwhelm the individual. I show further that the Greek romances engage in a type of talking cure: the novels use narration and story-telling to help assert the protagonists’ distance from their past traumatic experiences and, thus, allow the individual to overcome their painful past.